Non-invasive scoring systems of liver fibrosis predict prognosis in the cohort with myocardial infarction - Esther Wong; Yiming Chen; Gwyneth Kong; Jobelle Chia; Audrey Zhang; Anurag Mehta; Jayanth Jayabaskaran; Bryan Chong; Grace Cao; Benjamin Nah; Mark Yan-Yee Chan; Mark Muthiah; et al. (Scientific Reports)
Abstract Patients with liver fibrosis and type 2 diabetes mellitus (T2DM) have an increased risk of cardiovascular events. However, long-term prognosis of liver fibrosis and T2DM after acute myocardial infarction (AMI) remain to be investigated. This study compared clinical characteristics and prognosis of AMI patients with T2DM and evidence of liver fibrosis. Patients were stratified into low, intermediate and high-risk for fibrosis, using serum-based non-invasive tests (NITs): Fibrosis-4 Index (FIB-4), Aspartate Aminotransferase to Platelet Ratio Index (APRI) and Non-alcoholic Fatty Liver Disease Fibrosis Score (NFS). The primary outcome was all-cause mortality, Kaplan-Meier curves were constructed for 5-year all-cause mortality. Cox regression analysis was used to determine the independent predictors of mortality, adjusting for confounders. Out of 3287 AMI patients, 1547 were stratified as high-risk by any NIT (mean follow-up duration 2.7 ± 2.3 years). A dose-response relationship was found with increasing mortality risk for higher APRI and NFS scores. High-risk FIB-4 also predicted mortality significantly (adjusted HR [aHR] 1.791, 95% CI 1.436–2.235, p < 0.001). High-risk FIB-4 and APRI independently predicted mortality regardless of T2DM status, while NFS only predicted mortality in T2DM patients. Following AMI, individuals stratified by FIB-4, APRI, NFS as high-risk for liver fibrosis were associated with excess long-term mortality (aHR 1.780, 95% CI 1.442–2.196, p < 0.001). Hence, readily available NITs may be beneficial in risk prognostication of AMI patients.